Mild features of partial PAX3 deletion in patients with prenatal Waardenburg syndrome: a case report and literature review - Chen, Qi; Shi, Lin; Chen, Yunpeng; Cao, Xinyu; Yang, Yan (Frontiers in Pediatrics, 2025)
BackgroundWaardenburg syndrome (WS) is a group of autosomal dominant hereditary disorders characterized by auditory–pigmentary abnormalities. Haploinsufficiency of paired box 3 (PAX3) gene is one of the known pathogenic mechanisms. However, clinical phenotypes are difficult to predict precisely in fetuses harboring PAX3 haploinsufficiency. In this study, we report a family with a PAX3 deletion encompassing exons 1–4, in which clinical manifestations ranged from normal to mild abnormalities.Case presentationA 22-year-old woman (gravida 2, para 0) was referred to our prenatal center at 18 weeks of gestation due to a history of congenital spina bifida in her previous pregnancy. Chromosomal analysis had been performed on fetal tissue from the terminated pregnancy and on amniotic fluid obtained during the current pregnancy. A rare partial deletion of PAX3 gene was identified and confirmed to be of paternal origin. A diagnosis of WS was established based on the clinical features of the father. However, the newborn from the second pregnancy exhibited normal phenotypes after birth.ConclusionThis work suggests that deletions encompassing the promoter and functional domains of PAX3 gene functionally represent a haploinsufficiency mechanism, which leads to variable clinical manifestations. These findings broaden our understanding of copy number variation analysis and genetic counseling in prenatal settings. In addition, PAX3 gene should be considered a candidate gene in cases presenting with auditory–pigmentary abnormalities or neural tube defects of unknown etiology.